PENERAPAN BUDIDAYA SAYURAN MELALUI MODIFIKASI POLA TANAM TUMPANGSARI DI DESA SOKAWERA, KECAMATAN CILONGOK, BANYUMAS - Sakhidin Sakhidin; Etik Wukir Tini; Wilujeng Hidayati; Nindy Sevirasari (Jurnal Abdi Insani, 2025)
The Women Farmers Group KUB YASINTA in Sokawera Village, Cilongok Subdistrict, Banyumas Regency, is a farmer group that provides food for families and improves the surrounding community's welfare. However, they have limited knowledge and skills in applying cultivation technology, which has resulted in suboptimal productivity in their farming businesses. This community service activity introduced appropriate technology in the intercropping pattern. The community service activities will be carried out from May to September 2025. The implementation methods included socialization, counseling, practice of intercropping chili, eggplant, spinach, and water spinach, and the creation of demonstration plots as a means of direct learning. Activity results showed respondents experienced a 39.7% increase in their understanding of the concept of intercropping. Before the training, only 63% of respondents understood intercropping, and after the training, the respondents' understanding increased to 88%. Intercropping has the potential to increase productivity and diversify agricultural yields. The Women Farmers Group members have understood the concept, objectives, and advantages of cultivation through the application of intercropping patterns, the selection of intercrops, the implementation of cultivation, and plant care using intercropping patterns. This activity is expected to become a model for sustainable farming based on local resources, which can be replicated in other areas with similar characteristics, while contributing to food security and increasing farmers' family income.